Attitudes of The University of Nahrain Officials and Students Towards Non – Class Activity - Hamid, Ziyad (Journal of Physical Education, 2019)
This study aims to identify the attitudes of officials and students at Nahrain university towards non – class activity .The study was conducted on a sample of (25) officials in colleges and (400) male and female students. The sample was divided into two groups representing the officials and students of the university. The researcher used the descriptive method for its relation to the nature of research. The scale has three axes: the trend towards the concept of non – class activity and the direction towards the role of the university in the interest of non – class activity. The importance of non – class activity and the results showed statistically significant differences between the attitudes of students and officials.